Analisis Penerapan Prosedur Persiapan Ruang Muat di MV. Manalagi Asta - Andi Fithrawan A. Djaelani (Lembaga Yasin AlSys, 2026)
Cargo hold preparation is an important stage in bulk carrier operations because hold cleanliness, equipment readiness, and crew compliance with Standard Operating Procedures (SOPs) determine loading readiness and the smooth operation of the vessel. This study aims to analyze the implementation of cargo hold preparation procedures on MV Manalagi Asta, identify the factors causing their suboptimal implementation, and formulate corrective actions to support loading readiness. This study employed a qualitative approach with a descriptive method. Primary data were obtained through direct observation during sea practice and interviews with the Chief Officer, boatswain, and deck crew, while secondary data were derived from ship documents, operational records, visual documentation, books, and relevant scientific literature. The data were analyzed through the stages of reduction, presentation, and conclusion drawing. The results showed that cargo hold preparation had not been implemented optimally, as indicated by the presence of previous cargo residues in the holds and bilge wells and inadequate maintenance of several hatch cover components. Work implementation was constrained by limited time, an imbalance between the number of deck personnel and the size of the work area, inadequate cleaning equipment, delays in equipment procurement, inconsistent supervision, and incomplete implementation of SOPs. These conditions reduced the thoroughness of the cleaning process, resulting in cargo holds that did not meet cleanliness standards. Corrective actions included conducting a safety meeting before work commenced, systematically preparing a work plan, clearly assigning responsibilities, strengthening phased inspections by the Chief Officer, implementing preventive maintenance, providing adequate cleaning equipment, and conducting final verification using a cargo hold preparation checklist. This study concludes that cargo hold preparation needs to be managed as a loading-readiness control system that integrates procedures, personnel, equipment, supervision, occupational safety, and documentation. These findings can provide a practical basis for shipping companies and ship crews to improve the effectiveness of cargo hold preparation and minimize the risks of loading delays and rejection.